2022
DOI: 10.1128/spectrum.01472-22
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Approach to Capture the Essence of Candida albicans Morphologies

Abstract: The fungus Candida albicans can “shape shift” between 12 morphologies in response to environmental variables. The cytoprotective capacity provided by this polymorphism makes C. albicans a formidable pathogen to treat clinically.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
2
2
0
Order By: Relevance
“…Moreover, an explanation for this phenomenon can be that C. albicans displays the ability to transition among different morphological forms, such as yeast, pseudohyphae, and hyphae, which is in agreement with what is stated above [80,81]. This morphological flexibility, also known as morphological plasticity, enables the fungus to adjust to diverse environments, enhancing its capacity to establish persistent infections and contribute to its resistance compared to other Candida species [80,81]. The CH polymer did not show activity for the tested bacteria or yeast in the concentration range evaluated, which is in line with the findings of Davoodbasha et al (2018), who found MIC values for E. coli and S. aureus between concentrations of 80 and 160 µg/mL and high MIC values for C. albicans [82].…”
Section: Antimicrobial Activity Of Ag-nps and The Developed Nanoconju...supporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, an explanation for this phenomenon can be that C. albicans displays the ability to transition among different morphological forms, such as yeast, pseudohyphae, and hyphae, which is in agreement with what is stated above [80,81]. This morphological flexibility, also known as morphological plasticity, enables the fungus to adjust to diverse environments, enhancing its capacity to establish persistent infections and contribute to its resistance compared to other Candida species [80,81]. The CH polymer did not show activity for the tested bacteria or yeast in the concentration range evaluated, which is in line with the findings of Davoodbasha et al (2018), who found MIC values for E. coli and S. aureus between concentrations of 80 and 160 µg/mL and high MIC values for C. albicans [82].…”
Section: Antimicrobial Activity Of Ag-nps and The Developed Nanoconju...supporting
confidence: 91%
“…Nucleatum, S. aureus, Staphylococcus epidermidis, Streptococcus mutans, Streptococcus oralis, and Veillonella dispar, and found that the bacterial strains were more susceptible to their Ag-NPs [78]. Moreover, an explanation for this phenomenon can be that C. albicans displays the ability to transition among different morphological forms, such as yeast, pseudohyphae, and hyphae, which is in agreement with what is stated above [80,81]. This morphological flexibility, also known as morphological plasticity, enables the fungus to adjust to diverse environments, enhancing its capacity to establish persistent infections and contribute to its resistance compared to other Candida species [80,81].…”
Section: Antimicrobial Activity Of Ag-nps and The Developed Nanoconju...supporting
confidence: 88%
“…Control staining with CW allowed for cell visualization regardless of their respective viability and vitality states. Moreover, since this dye is specific for cell wall chitin, alterations in cell morphology after treatments could also be evaluated [ 5 , 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…
Phenotypic plasticity, the ability of a single genotype to generate different phenotypes in response to environmental stimuli, allows microorganisms to adapt quickly to their changing environment and thrive in specific ecological niches. The human pathogenic yeast Candida albicans can switch among various morphological phenotypes in response to different environmental cues (Bettauer et al, 2022). This ability to grow in different forms is crucial for its commensal lifestyle and pathogenicity (Noble et al, 2017).
…”
mentioning
confidence: 99%